THE PREVALENCE OF MANDIBULAR MIDLINE DEVIATION IN CHILDREN AND ADOLESCENTS WITH DIFFERENT TYPES OF MALOCCLUSIONS - Andreea Raluca Hlatcu; Elena Galan; Elina Teodorescu; Stefan Milicescu; Mariana Păcurar; Manuela Chibelean; Ecaterina Ionescu (Romanian Society of Oral Rehabilitation, 2023)
In this study, the prevalence of mandibular midline deviation in different types of malocclusions were evaluated taking into account sexual dimorphism in patients with mixed and permanent dentition. With the aforementioned aim, a cross-sectional study was carried out on a total of 214 patients (134 females and 80 males) aged between 7-15 years (with a mean age of 9.5 ± 2 years). On the study casts of each subject participating in the study, the displacement of the lower dental midline compared to the upper one was measured in different classes of malocclusion, taking into account sexual dimorphism. Three study groups were formed: first with mandibular midline deviation with values less than 2 mm, second with deviation between 2-4 mm and third with deviation more than 4 mm. Subsequently, the prevalence of the displacement of the lower dental midline was assessed taking into account the sexual dimorphism and the Angle classes malocclusions analyzed (Angle Class I, II/1, II/2, III) and UPC (unilateral posterior crossbite). Mandibular midline deviation greater than 2 mm was observed in more than three quarters (75.7%) of the patients in the studied group. In the five classes of malocclusion, a higher frequency of displacement of the lower dental midline was appreciated in the range of 2-4 mm of 59.8%. In this interval, the highest percentage of displacement was observed in Angle Class II/1 (18.2%), followed by unilateral posterior crossbite UPC (15%) and Angle Class II/2 (13.1%). Most large displacement of the lower dental midline (with a value more 4 mm) was recorded in unilateral posterior crossbite UPC (5.6%). Although the displacement of the mandibular midline was recorded in a slightly increased percentage in males (61.25%) compared to the group of females (58.95%), from a statistical point of view, no notable differences were reported between the two genders. Dental midline deviation changes should be noted and analyzed from the beginning of orthodontic treatment in order not to cause later functional or aesthetic disorder.